Protease Inhibitor-Dependent Inhibition of Light-Induced Stomatal Opening - Wang, Tenghua; Ye, Wenxiu; Wang, Yin; Zhang, Maoxing; Aihara, Yusuke; Kinoshita, Toshinori (Frontiers in Plant Science, 2021)
Stomata in the epidermis of plants play essential roles in the regulation of photosynthesis and transpiration. Stomata open in response to blue light (BL) by phosphorylation-dependent activation of the plasma membrane (PM) H+-ATPase in guard cells. Under water stress, the plant hormone abscisic acid (ABA) promotes stomatal closure via the ABA-signalling pathway to reduce water loss. We established a chemical screening method to identify compounds that affect stomatal movements in Commelina benghalensis. We performed chemical screening using a protease inhibitor (PI) library of 130 inhibitors to identify inhibitors of stomatal movement. We discovered 17 PIs that inhibited light-induced stomatal opening by more than 50%. Further analysis of the top three inhibitors (PI1, PI2, and PI3; inhibitors of ubiquitin-specific protease 1, membrane type-1 matrix metalloproteinase, and matrix metalloproteinase-2, respectively) revealed that these inhibitors suppressed BL-induced phosphorylation of the PM H+-ATPase but had no effect on the activity of phototropins or ABA-dependent responses. The results suggest that these PIs suppress BL-induced stomatal opening at least in part by inhibiting PM H+-ATPase activity but not the ABA-signalling pathway. The targets of PI1, PI2, and PI3 were predicted by bioinformatics analyses, which provided insight into factors involved in BL-induced stomatal opening.